A hybrid MADM analysis in evaluating process of chemical wastewater purification regarding to advance oxidation processes. Issue 3 (3rd July 2017) - Khodadadi, Mohamad Reza; Hashemkhani Zolfani, Sarfaraz; Yazdani, Morteza; Zavadskas, Edmundas Kazimieras
Abstract: Organic components, widely spread in water by industrial sources become emerging Contaminants in the water. Due deficient removal in conventional wastewater treatments, advanced treatment should be considered for industrial wastewaters removing. Advance oxidation processes (AOPs) can be used as an effective subset of chemical treatment for degradation of toxic from water in industrial processing plant. Two Multiple Criteria Decision Making (MCDM) methods based on hybrid SWARA-WASPAS are organized to investigate efficiency of different sort of AOPs: ozonation, fenton, electrochemical Oxidation, UV/Photo-catalysis, UV/H2 O2 . Based on MCDM, Fenton is the most possible AOPs for application in wastewater treatment areas. In this study, SWARA is deployed in evaluating criteria that were identified in literature review, and WASPAS is used for evaluating and ranking the methods. The main point of this study is based on real data.